2011
DOI: 10.1002/dvdy.22619
|View full text |Cite
|
Sign up to set email alerts
|

Msx1 and Msx2 in limb mesenchyme modulate digit number and identity

Abstract: Msx1 and Msx2 encode homeodomain transcription factors that play a crucial role in limb development. However, the limb phenotype of the double Msx1 null/null Msx2 null/null mutant is difficult to analyze, particularly along the anteroposterior axis, because of the complex effects of the double mutation on both ectoderm-and mesoderm-derived structures. Namely, in the mutant, formation of the apical ectodermal ridge (AER) is impaired anteriorly and, consequently, the subjacent mesenchyme does not form. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 53 publications
5
31
0
Order By: Relevance
“…This is consistent with previous reports showing overlapping expression of Lhx2 and Msx1 genes at the leading edge of mouse limb buds, and coexpression of their fly orthologues in Drosophila wing discs [12]. Our finding is also consistent with the observation that limb development is severely impaired in Msx1/Msx2 double knockout mice [22,25] and Lhx2/Lhx9 double knockout mice [13]. Among 11 LIM homeobox transcription factors, Lhx9 is phylogenetically closest to Lhx2 [26]; thus it is likely that Lhx9 activity is complementary to Lhx2-mediated induction of Msx1/Msx2 expression.…”
Section: Discussionsupporting
confidence: 95%
“…This is consistent with previous reports showing overlapping expression of Lhx2 and Msx1 genes at the leading edge of mouse limb buds, and coexpression of their fly orthologues in Drosophila wing discs [12]. Our finding is also consistent with the observation that limb development is severely impaired in Msx1/Msx2 double knockout mice [22,25] and Lhx2/Lhx9 double knockout mice [13]. Among 11 LIM homeobox transcription factors, Lhx9 is phylogenetically closest to Lhx2 [26]; thus it is likely that Lhx9 activity is complementary to Lhx2-mediated induction of Msx1/Msx2 expression.…”
Section: Discussionsupporting
confidence: 95%
“…The complex synpolydactyly of the hands in P2 is reminiscent of hand malformations caused by spatiotemporal disruption of Hedgehog signalling. Recently, it has been shown that Msx1 and Msx2 expression in the limb mesenchyme modulates digit number and identity via the Shh and Bmp signalling pathways 28. The forelimb phenotype in these mice shows striking similarities to the complex synpolydactyly of the hands which we observed in P2.…”
supporting
confidence: 60%
“…Double knock out of Dlx5/6 in mice resulted in phenotypes similar to human SHFM1 [Merlo et al, 2002;Robledo et al, 2002]. Double inactivation of Msx1 and Msx2 in mice caused polydactyly in the forelimbs and oligodactyly in the hindlimbs [Lallemand et al, 2005;Bensoussan-Trigano et al, 2011]. Triple knockout mice involving Msx1 , Dlx5 , and Dlx6 developed phenotypes similar to those of Msx1 and Msx2 double knockout mice, while phenotypes of Msx2 , Dlx5 , and Dlx6 triple knockout mice were similar to Dlx5/6 double knockout mice.…”
Section: Mutation Screeningmentioning
confidence: 91%